2010
DOI: 10.1002/ana.22018
|View full text |Cite
|
Sign up to set email alerts
|

Environmental neurotoxin‐induced progressive model of parkinsonism in rats

Abstract: Objective Exposure to a number of drugs, chemicals or environmental factors can cause parkinsonism. Epidemiologic evidence supports a causal link between the consumption of flour made from the washed seeds of the plant, Cycas micronesica, by the Chamorro population of Guam and the development of Amyotrophic Lateral Sclerosis/Parkinsonism Dementia Complex (ALS/PDC). Methods We now report that consumption of washed cycad flour pellets by Sprague-Dawley male rats induces progressive parkinsonism. Results Cyca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 44 publications
1
37
0
Order By: Relevance
“…Furthermore, these animals did not show advanced symptoms (i.e., motor disturbances) of the disease. It is only at later time points (thirty-six weeks after cycad exposure) that cycad-fed rats display a significant loss of DA neurons in the SN and the presence of α-synuclein aggregation, a classical histological hallmark of PD (Shen et al, 2010). In other words, cycad consumption in rats induces a hypersomnia that precedes the development of parkinsonian symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, these animals did not show advanced symptoms (i.e., motor disturbances) of the disease. It is only at later time points (thirty-six weeks after cycad exposure) that cycad-fed rats display a significant loss of DA neurons in the SN and the presence of α-synuclein aggregation, a classical histological hallmark of PD (Shen et al, 2010). In other words, cycad consumption in rats induces a hypersomnia that precedes the development of parkinsonian symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Flour made from the seeds of the plant C ycas micronesica was fed in pellet form to induce a Parkinsonian-like behavior in rats (Shen et al, 2010, in press). Briefly, pellet batches were prepared every other week for control and experimental rats, using unbleached wheat flour or washed cycad flour, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of adult rodents have focused on the carcinogenic potential of cycad and cycasin, although cerebellar pathology was reported in a study of rats fed L-BMAA [55]. A recent experimental study of rats fed cycad materials (cycasin content unknown) found neuropathological changes in the substantia nigra, striatum, locus coeruleus and cingulate cortex [56] which, as the authors note, supports the proposed role of cycad in western Pacific ALS-PDC, a proposal first made by Whiting and Kurland, later resurrected by Spencer and colleagues, and now once again the subject of intense biomedical interest. Shaw and his colleagues, the authors of the recent rodent study, propose that cycad sitosterols—either as the free sterol or the glucoside—are likely etiological agents; this seems unlikely since these compounds are used to treat prostatic hypertrophy without reported neurological disease, and controlled toxicological studies have given these sterols a clean bill of health [57].…”
Section: Evidence For the Role Of Cycads In Als-pdcmentioning
confidence: 99%
“…After 5 days, lung samples were inflated, fixed in formalin, paraffin-embedded, and sectioned for histological analysis. Slides were washed and counterstained with hematoxylin and eosin [21].…”
Section: Lung Tissue Histologymentioning
confidence: 99%